Life Cycle Of Culuwiya Tilapiae (Nasir y Gómez, 1976) (Trematoda: Haploporidae) In Venezuela - Díaz, Marcos T.; Bashirullah, Abul K.; Hernández, Luz E.; Gómez, Erika (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Lisbe 11.5606 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The life cycle of Culuwiya tilapiae (Nasir y Gómez, 1976) Overstreet and Curran, 2005, a digenean belonging to the family Haploporidae Nicoll, 1914 is redescibed and illustrated. The parasite infects naturally the snail, Pyrgophorus cf. spiralis (Guppy 1864), and the definitive host, Oreochromis mossambicus (Peters, 1852). Both molluscs and fish were collected from the Parque Litoral Laguna de los Patos, Cumaná, Estado Sucre, Venezuela. The cercariae were developed in redia in the digestive gland of molluscs and encysted on the water surface and more frequently on the bottom and walls of dishes. The 2-4 days old cysts of C. tilapiae were fed to laboratory reared O. mossambicus, and the trematode reaches sexual maturity in 22-32 days after the experimental infection. All developmental stages of C. tilapiae are described and illustrated. This species was compared with other members of Culuwiya and with Saccocoelioides tarpazensis Díaz and Gonzalez, 1990, for being the only recorded haploporids species in Venezuela and its life cycle had been elucidated and for the similarity with C. tilapiae. This species is redescribed herein represents the first record of Culuwiya Overstreet and Curran, 2005 in Venezuela